A Psychometric Assessment of the Psychological and Social Well-Being Indicators in the PINE Study. (October 2014) - Chang, E-Shien; Beck, Todd; Simon, Melissa A.; Dong, XinQi
Objective: This report aims to establish the reliability and validity of five psychological and social well-being indictors in their applications to a U.S. Chinese aging population.Method: The Population Study of Chinese Elderly in Chicago (PINE) is a population-based epidemiological study of Chinese older adults in the Greater Chicago area. Internal consistency reliability was assessed by determining the coefficient alpha and inter-item correlation coefficients. Content validity was assessed by bilingual and bicultural study researchers and community leaders.Results: The reliability and validity analysis supported the use of the Chinese version of the psychological and social well-being indicators in the PINE study. The value of Cronbach's alpha for fives scales ranged from .64 to .82, indicating reasonable internal consistency. Content validity was established through intensive review by a panel of experts.Discussion: The instruments discussed in this report are reliable and valid measures to assess key dimensions of psychological and social distress of Chinese older adults.